How companies choose their type of funding: Aeronautical Industry? - EL ALAOUI, HAMZA; MAKAYSSI, Khansâa; KABBAJ, Smail (Revue du contrôle, de la comptabilité et de l’audit, 2020)
In this Paper, we seek to focus on the determinants that interfere in the evaluation of investment projects in aeronautical activity in Morocco, and this by exploring the temporal and spatial dimensions of their financing, as well as putting emphasis on the role that the management control function can play in supporting this implementation process.